The Utilization of Chain Word Games to Improve Senior High School Students’ English Vocabulary Mastery - Listyowati, Rini; Anis Jumatus Solehah, Sitti; Rohaniyah, Jaftiyatur (Universitas Nusantara PGRI Kediri, 2023)
Vocabulary is very important to be mastered by who are learning foreign language, especially for students at Senior High School. This research was conducted at MA Miftahul Qulub Polagan. Most of the students at MA Miftahul Qulub Polagan get difficulties in mastering English vocabulary. It was caused by the method in teaching vocabulary. So, the students felt boring and did not have motivation in learning vocabulary. Therefore, learning innovation is needed to build their motivation in learning vocabulary. This research conducted chain word games to improve students’ vocabulary mastery. The research design is classroom action research which has two cycles implementation. Test and observation were utilized to gather the data. The research performed that the students’ vocabulary mastery increased in each cycle such as in cycle 1 was 34% students who reached the comulative score and cycle II was 49% students who reached comulative score. Cycle I showed the average score of students' mastery was 67, and cycle II showed the average score 76. It can be concluded that Word Chain Game can improve students' vocabulary mastery.